Milk production and its relationship with milk composition, body and udder morphological traits in Bedouin goat reared under arid conditions - Kouri, Fatima; Charallah, Salima; Kouri, Amina; Amirat, Zaina; Khammar, Farida (Acta Scientiarum. Animal Sciences, 2018)
This research aims to assess the performances of lactating Bedouin goat under arid conditions, focusing on the relationship of milk yield with body and udder morphology and growth traits. Fourteen goats and their kids were followed during early lactation (90 days post-partum). Mean daily milk yield was 0.56 kg. Milk fat, proteins, lactose, solids non-fat and minerals were respectively 34.9, 38.9, 48.8, 107 and 6.7 g L-1. Mean kids’ birth weight, adjusted body weight at 90 days of age and average daily gain were respectively 2 kg, 6.6 kg and 51.4 g day-1. Daily milk yield was correlated with goats’ body weight, withers height, rump height, udder width and udder circumference but not with linear udder score and growth performances. These results provide important data about the milk production of Bedouin goat emphasizing its correlation with body and udder morphological traits which can help to elaborate a specific breeding program for this breed.